Characters of Colour - Brissett, Marilyn M. (Qualitative and Quantitative Methods in Libraries, 2019)
The purpose of this qualitative content analysis is to determine if the picture book collection at the Gladys A. Abraham Elementary School Library accurately reflects and therefore serves the needs of the majority of its students. A disparity exists between the actual ethnicities represented by the school population and those depicted in the picture book collection. Less than ten percent of the books most frequently selected by kindergarten through 3rd grade students depict realistic stories and a disproportionate percentage (88%) of books have settings in the United States. This study can be used as a model to examine elementary school libraries on each of the three main islands (St. Croix, St. John, and St. Thomas) to identify how well their collections reflect the ethnicities of their students.